Soliton solutions for system of ion sound and Langmuir waves - Mohammed, Wael W.; Abdelrahman, Mahmoud A. E.; İnç, Mustafa; Hamza, A. E.; Akinlar, Mehmet Ali (Springer, 2020)
We study on constructing new traveling wave solution of a system known as ion sound and Langmuir waves by using method of extended Jacobian elliptic function expansion and He's semi-inverse technique. Some new solutions will be beneficial for researchers concerning with nonlinear physical phenomena. The proposed methods may serve as the framework for solutions of various equations in applied science. Graphical simulations are provided to illustrate the behavior of these solutions.
Keywords: Elliptic functions; Variational principles; Ion sound and Langmuir waves; Nonlinear physical phenomena; Dark and bright solitons; Traveling wave solutions